Oncogenic human papillomaviruses activate the tumor-associated lens epithelial-derived growth factor (LEDGF) Gene - Leitz, Jenny; Reuschenbach, Miriam; Lohrey, Claudia; Honegger, Anja; Accardi, Rosita; Tommasino, Massimo; Llano, Manuel; Knebel Doeberitz, Magnus von; Hoppe-Seyler, Karin; Hoppe-Seyler, Felix (PLoS pathogens, 2014)
The expression of the human papillomavirus (HPV) E6/E7 oncogenes is crucial for HPV-induced malignant cell transformation. The identification of cellular targets attacked by the HPV oncogenes is critical for our understanding of the molecular mechanisms of HPV-associated carcinogenesis and may open novel therapeutic opportunities. Here, we identify the Lens Epithelial-Derived Growth Factor (LEDGF) gene as a novel cellular target gene for the HPV oncogenes. Elevated LEDGF expression has been recently linked to human carcinogenesis and can protect tumor cells towards different forms of cellular stress. We show that intracellular LEDGF mRNA and protein levels in HPV-positive cancer cells are critically dependent on the maintenance of viral oncogene expression. Ectopic E6/E7 expression stimulates LEDGF transcription in primary keratinocytes, at least in part via activation of the LEDGF promoter. Repression of endogenous LEDGF expression by RNA interference results in an increased sensitivity of HPV-positive cancer cells towards genotoxic agents. Immunohistochemical analyses of cervical tissue specimens reveal a highly significant increase of LEDGF protein levels in HPV-positive lesions compared to histologically normal cervical epithelium. Taken together, these results indicate that the E6/E7-dependent maintenance of intracellular LEDGF expression is critical for protecting HPV-positive cancer cells against various forms of cellular stress, including DNA damage. This could support tumor cell survival and contribute to the therapeutic resistance of cervical cancers towards genotoxic treatment strategies in the clinic.
Gesehen am 10.08.2020